2013
DOI: 10.1074/jbc.m113.468686
|View full text |Cite
|
Sign up to set email alerts
|

The Src Homology 3 Domain-containing Guanine Nucleotide Exchange Factor Is Overexpressed in High-grade Gliomas and Promotes Tumor Necrosis Factor-like Weak Inducer of Apoptosis-Fibroblast Growth Factor-inducible 14-induced Cell Migration and Invasion via Tumor Necrosis Factor Receptor-associated Factor 2

Abstract: Background: Glioblastoma is characterized by heightened cell invasion and therapeutic resistance. Results: The Src homology 3 domain-containing GEF (SGEF) promotes fibroblast growth factor-inducible 14 (Fn14) proinvasive signaling in glioblastoma via TNF receptor-associated factor 2 (TRAF2). Conclusion: SGEF is an important regulator of glioblastoma cell invasion downstream of Fn14. Significance: Therapy directed at mediators of invasion may confer increased chemotherapeutic and radiologic susceptibility in gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 54 publications
1
49
0
Order By: Relevance
“…It has been reported that RhoG and SGEF promote cell migration and invasion in several cell lines including glioblastoma cells, MDA-MB-231 breast cancer cells, PC-3 prostate cancer cells and HeLa cells (Chatterjee et al, 2011;Fortin Ensign et al, 2013;Hiramoto-Yamaki et al, 2010;Katoh et al, 2006;Krishna Subbaiah et al, 2012;Kwiatkowska et al, 2012). Here, we also show that RhoG-and SGEF-deficient SUM159 cells show impaired invasion, despite showing enhanced invadopodia formation and ECM degradation.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It has been reported that RhoG and SGEF promote cell migration and invasion in several cell lines including glioblastoma cells, MDA-MB-231 breast cancer cells, PC-3 prostate cancer cells and HeLa cells (Chatterjee et al, 2011;Fortin Ensign et al, 2013;Hiramoto-Yamaki et al, 2010;Katoh et al, 2006;Krishna Subbaiah et al, 2012;Kwiatkowska et al, 2012). Here, we also show that RhoG-and SGEF-deficient SUM159 cells show impaired invasion, despite showing enhanced invadopodia formation and ECM degradation.…”
Section: Discussionsupporting
confidence: 75%
“…These actin-rich dorsal structures share several of its molecular components with invadopodia and podosomes, as well as with focal adhesions, suggesting that some of the signaling pathways controlling their assembly may also be conserved (Buccione et al, 2004). In addition, recent studies have shown that SGEF may play a role during invasion in human papillomavirus-mediated cervical cancer, prostate cancer and glioblastoma (Fortin Ensign et al, 2013;Krishna Subbaiah et al, 2012;Wang et al, 2013). The molecular mechanisms by which SGEF contributes to these processes are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Lentiviral vectors containing shRNA targeting SGEF (shSGEF-12 & shSGEF-13) or control empty vector (control) were obtained from Open Biosystems (Fisher Scientific, Pittsburgh, PA) and packaged for lentiviral production as previously described (12). …”
Section: Methodsmentioning
confidence: 99%
“…In GB tumors, SGEF has been shown to be significantly overexpressed, to be correlated with poor patient outcome, and to promote glioma cell migration (12). We report that SGEF expression is increased in a subset of TMZ-resistant derived primary GB xenografts and is up-regulated by TWEAK-Fn14 signaling via NF-κB activity.…”
Section: Introductionmentioning
confidence: 99%
“…Lamellipodia formation in glioma cells under PPF treatment was interrogated as described previously [25]. Briefly, glioma cells were plated onto 10-well glass slides pre-coated with 10 μg/ml laminin at the density of 3000 cells/well for 24 hours at 37°C.…”
Section: Methodsmentioning
confidence: 99%